Land fragmentation and off-farm labor supply in China - Lili Jia (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
This thesis focuses on testing whether land fragmentation in China has an impact on off-farm labor supply by utilizing a data set developed between 1995-2002 for the Zhejiang, Hubei and Yunnan Provinces of China. Adopting the institutional innovation theory and a microeconomic farm household model, the thesis contributes to improving the understanding of the current widespread phenomenon of land fragmentation in four aspects: the determinants of land fragmentation in China; a theoretical analysis of the effects of land fragmentation; estimating the effect of land fragmentation on agricultural labor productivity; and estimating the effect of land fragmentation on off-farm labor supply. First, an institutional innovation theory is introduced to analyze the determinants of land fragmentation in China. We find that the current land institution, which leads to land fragmentation, has its roots in the demand for land decentralization from farmers, but is constrained by incomplete property rights. Therefore, land reallocation does not necessarily increase land fragmentation, and whether the land market can reduce land fragmentation or not depends on the development of the local labor market. Second, the microeconomic farm household model is applied to aid in understanding the effects of land fragmentation on agricultural labor productivity and offfarm labor supply. The analysis shows that the effects of land fragmentation depend on the local shape of the production function. A positive effect of land fragmentation on agricultural labor productivity may increase the off-farm labor supply, while a negative effect suggests a decrease of off-farm labor supply, and the effect of off-farm labor supply may be neutral if the labor market is constrained. Third, a test for the effect of land fragmentation on agricultural labor productivity is conducted, and the result shows that the land fragmentation decreases agricultural labor productivity in general, implying an adoption of land consolidation. But this effect is only obvious in the Zhejiang province, where the labor market is better developed. Finally, a direct test for the effect of land fragmentation on off-farm labor supply is implemented. The findings indicate that the off-farm labor supply is not influenced by land fragmentation due to the constrained labor market, suggesting a need to further develop the labor market. Furthermore, the off-farm wage and educational levels play a role in increasing off-farm labor supply, while the land endowment intends to decrease it. – – Diese Arbeit behandelt die Frage, ob die Landfragmentierung in China einen Einfluss auf das außerlandwirtschaftliche Arbeitsangebot hat. Dazu werden Daten aus den chinesischen Provinzen Zhejiang, Hubei und Yunnan der Jahre 1995 bis 2002 herangezogen. Unter Anwendung der Institutionellen Innovationstheorie und des mikroökonomischen Haushaltsmodells trägt diese Arbeit dazu bei, vier Aspekte der Landfragmentierung besser zu verstehen: Die Determinanten der Landfragmentierung in China, die theoretische Analyse der Effekte der Landfragmentierung, empirische Schätzung des Effektes der Landfragmentierung auf die landwirtschaftliche Arbeitsproduktivität und Betrachtung der Auswirkungen der Landfragmentierung auf das außerlandwirtschaftliche Arbeitsangebot. Die gegenwärtigen Institutionen in der Landallokation, die zu dem hohen Grad der Landfragmentierung in China führen, haben ihre Wurzeln in der Nachfrage der Landwirte nach Landdezentralisierung. Problematisch hierbei sind die unvollständigen Eigentumsrechte. Aus diesem Grund steigert Landreallokation nicht notwendigerweise die Landfragmentierung. Die Frage, ob der Landmarkt Landfragmentierung reduzieren kann, hängt zudem von dem Entwicklungsstand des lokalen Arbeitmarktes ab. Zuerst wird in die Institutionelle Innovationstheorie eingeführt, um die Determinanten der Landfragmentierung in China zu herauszuarbeiten. In einem zweiten Schritt wird das mikroökonomische Haushaltsmodell für landwirtschaftliche Haushalte angewandt, um Erkenntnisse über die Effekte der Landfragmentierung auf landwirtschaftliche Arbeitsproduktivität und das außerlandwirtschaftliche Arbeitsangebot zu erlangen. In den Analyseergebnissen kann gezeigt werden, dass die Effekte der Landfragmentierung von der Ausprägung der lokalen Produktionsfunktion abhängen. Eine positive Auswirkung der Landfragmentierung auf landwirtschaftliche Arbeitsproduktivität lässt das außerlandwirtschaftliche Arbeitsangebot der Haushalte steigen. Eine negative Auswirkung dagegen zeigt eine Verringerung des außerlandwirtschaftlichen Arbeitsangebotes. Neutrale Konsequenzen gehen von einem eingeschränkten Arbeitsmarkt aus. An dritter Stelle wird ein Test mit dem Ziel durchgeführt, den Effekt der Landfragmentierung auf landwirtschaftliche Arbeitsproduktivität herauszufinden. Die Ergebnisse zeigen, dass die Landfragmentierung im Allgemeinen die landwirtschaftliche Arbeitsproduktivität reduziert, wenn man einen Landkonsolidierungsprozess annimmt. Allerdings ist dieser Effekt nur für die Provinz Zhejiang eindeutig, wo der Arbeitsmarkt besser entwickelt ist. Schließlich wird ein direkter Test des Einflusses von Landfragmentierung auf das außerlandwirtschaftliche Arbeitsangebot implementiert. Die gewonnenen Erkenntnisse deuten darauf hin, dass das außerlandwirtschaftliche Arbeitsangebot wegen des begrenzten Arbeitsmarktes nicht von der Landfragmentierung beeinflusst wird. Dies deutet darauf hin, dass eine Weiterentwicklung des Arbeitsmarktes unabdingbar ist. Außerdem spielen das außerlandwirtschaftliche Lohnniveau und das Bildungsniveau eine Rolle dabei, das außerlandwirtschaftliche Arbeitsangebot zu vergrößern, wogegen eine ausreichende Ausstattung mit Land es eher verringert.
urn:nbn:de:gbv:3:2-18757
Keywords: 330